Ger(aç@es): a gestão de competências no contexto das gerações Baby Boomers, X e Y na Universidade Estadual da Paraíba - Luz, José Lucas Gouveia da Silva Graciano e (2018)
In the 21st Century scenario, scientific-technological evolution, associated with the phenomena of network information and the globalization of business and culture, has contributed to the re-articulation of the new civilizing order, which has a strong repercussion in the world of work, organizations and in professions, focusing on the (re)formatting of generations. In the context of people management, three categories are found in the job market: a) professionals of the Baby Boomers Generation, whose expertise has constituted the history and development of organizations over time; b) professionals of Generation X, disciplined heirs of the experiences of those who preceded them; and c) Generation Y professionals, dynamic and much more adapted to the technological reconfigurations of the digital culture. As a result, this research aims to analyze the management of competences in the context of the Baby Boomers, X and Y generations, at the Universidade Estadual da Paraíba (UEPB), Brazil. In methodological terms, this is a field research, of quantitativequalitative approach, descriptive-type, whose probabilistic stratified of proportional fraction samplings were selected a sample one corresponding to 232 technical-administrative servers, in front of a universe of 660 university employees, to whom a mixed questionnaire was applied. The research also worked with 28 managers of the central administration, to whom the trie hierarchical research instrument was applied. For the organization and treatment of these data, the research was based on content analysis. In the results spectrum, the research identified a tendency, for part of the UEPB managers, in adopt a traditional/technical management model, to the detriment of a management based on the identification and development of talents and competence. Regarding the technical-administrative servants, these have demonstrated more importance to the skills friendliness, responsibility, professional ethics, focus on quality of service and teamwork, which demonstrates certain affinity with the most modern management models. About generations, it was found that, in the Y generation there were no major changes in relation to the general average, with the same competencies as the five most important. In the X generation, teamwork gave way to interpersonal relationships, among the five most important. The Baby Boomers, on the other hand, have given more importance to the competence to circumvent unforeseen matters of cordiality. In general, there was a friction between the management model adopted by the managers and the one desired by the technical servers. However, the data did not show a great divergence of thinking among the different generations that compose UEPB's technicaladministrative staff, in terms of the most important competences, in the face of the university's strategic objectives.